Acoustomagnetic Registration of Magnetic Nanoparticles in a Liquid Medium - Аврунін, О. Г.; Avrunin, O. G.; Bondarenko, I. S.; Rakhimova, M. V.; Bondarenko, S. I.; Krevsun, A. V.; Kulish, S. M. (Begell House, Inc, 2019)
The technique and results of experiments on the registration of magnetic nanoparticles in a colloidal solution using the combined effect of ultrasound and a direct magnetic field are presented. The possibility of using this technique to control the content of magnetic nanoparticles in a biological substance is discussed.
Keywords: magnetic nanoparticles; ultrasound; direct magnetic field; biological substance; colloidal solution